Kesetaraan gender di perguruan tinggi Islam = baseline and Institutional analysis for gender mainstreaming in IAIN Sunan Kalijaga - H. M. Amin Abdullah (UIN Sunan Kalijaga Press, 2004)
ws.c.1-3/oen, .04-.06/ws.c.7